A STUDY OF THE MISTAKES IN THE ENGLISH TRANSLATION OF THE INDONESIAN MINOR THESIS’ TITLES IN BUSINESS ADMINISTRATION STUDY PROGRAM IN POLITEKNIK LPKIA BANDUNG - Tjang Kian Liong (Universitas Widyatama, 2023)
Students in the Business Administration Study Program in LPKIA Bandung must do their final projects as one of the requirements before graduating from the D-3 program. This final project is called minor thesis and is written in the Indonesian language. It is a custom practice that the titles and abstracts of the minor thesis be written in both Indonesian and English languages. As the students mostly have limitation in their capability to write in English, many of them just translate the titles and abstracts, for example by using the Google’s translation services. Hence, there is a great possibility the translation will be incorrect; some words or expressions may not be translated correctly to conduct the originally intended meanings of the authors. Additionally, it sometimes happens that students just misperceive the meanings of certain words, for instance, the Indonesian word ‘pengelolaan’ may simply be used and interpreted as ‘management’ while students may actually want to discuss about ‘penanganan’ or ‘handling’ of a certain task or procedure. This study uses the descriptive analysis method to unveil common mistakes made by students when translating their minor thesis’ titles from Indonesian to English, to discuss and offer better English choices of words for their translation, and to provide a reference so that students in the future can avoid similar mistakes when they write their minor thesis’ titles in English